Teaching Vocabulary Through Sentences - tosuncuoglu, irfan (Journal of History Culture and Art Research, 2015)
Teaching Vocabulary Through Sentences Abstract Almost every teacher is certain about that vocabulary is an important facet of learning a second language. It may be more important than grammar, at least in so far as this concerns communication , and particularly in the early stages when learners seem to understand that amassing a basic vocabulary is very important to fluency in another language. As a rule, receptive vocabulary exceeds productive vocabulary and why listening with comprehension and speaking with comprehension are two very different things—the latter a more difficult cognitive process than the former. Furthermore, vocabulary acquisition is highly idiosyncratic and depends largely on the learner and her or his individual learning styles and cognitive abilities. No two people learn alike. In particular, as understanding and fluency increases, individual interests and even needs will change, which then requires teacher-assisted guidance and remediation vis-à-vis the compilation of a specified and nuanced vocabulary that is tailored to the learner’s more practical linguistic needs, whatever these might be. Cümleler Yoluyla Kelime Öğretimi Öz Öğretmenler, ikinci bir dil öğrenmede kelimenin önemli bir yere sahip olduğu konusunda neredeyse hemfikirdirler. Kelime birikiminin, dilde akıcılık için önemli bir faktör olması sebebiyle, dilbilgisinden daha önemli yere sahip olduğu söylenebilir. Kural olarak, algısal kelime bilgisi oranı üretimsel kelime bilgisini geçmekte ve dinleme kavrama ve konuşma kavrama iki farklı unsur olup ve burada ikinci saydığımız unsur birincisinden daha zor bir bilişsel işlevselliğe sahiptir. Bundan başka, kelime edinimi yüksek derecede kendine özgü olup öğrenene, öğrenenin öğrenme tarzına ve bilişsel kabiliyetine büyük ölçüde bağlıdır. Hiç bir insan aynı değildir. Özellikle anlama ve akıcılık arttığında, bireysel ilgiler ve hatta ihtiyaçlar değişecek, daha sonra öğretmen destekli rehberliğe ihtiyaç duyulacak ve karşılıklı iletişimle ve her ne için olursa olsun öğrencinin dilbilimsel ihtiyaçlarına göre belirlenen detaylı kelime bilgileri daha iyi bir seviyeye gelebilecektir. Bu makalede, kelimelerin cümleler yoluyla nasıl öğretilebileceği konusu araştırılmıştır.